Application of different combinations of lactic acid, phototrophic bacteria and yeast mixtures in control of seed and seedlings pathogens of tomato and pepper - Ristić Danijela (Institute of Pesticides and Environmental Protection, 2021)
Application of three combinations of lactic acid bacteria (Lactobacillus plantarum, Lactobacillus rhamnosus), phototrophic bacteria (Rhodopseudomonas palustris) and yeast (Saccharomyces cerevisiae) with sugar cane molasses, marked as: EM1, EM5 and EM AGRO, against the phytopathogenic fungi of tomato and pepper: Fusarium oxysporum, Alternaria alternata, Botrytis cinerea, Colletotrichum sp., Verticilium dahliae and Pythium aphanidermatum was evaluated in vitro and in vivo. A combination of bacteria and yeast named EM5 showed the highest mycelium growth inhibition against B. cinerea (38.4%) in a double agar diffusion test. In a microdilution test, the combination EM1 showed the highest inhibitory effect on B. cinerea (MIC 1x10-3 ml/ml), while EM5 showed a similar inhibitory effect towards F. oxysporum, A. alternata and Colletotrichum sp. (MIC 10 ml/ml). The use of EM1 (in concentrations 10 and 100 µl/ml) and EM AGRO (10 µl/ml) is recommended for tomato seedling protection. EM1 (100 µl/ml), EM5 and EM AGRO (10 µl/ml) are recommended for pepper seedling protection.